2019
DOI: 10.1186/s40561-019-0093-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of awarding badges on Student’s engagement in Gamified e-learning systems

Abstract: Gamification has been gaining increasing acceptability in recent times in educational and commercially related activities, as a tool that encourages and improves the motivation of digital native learners. Since learners can easily engage, educationists have explored gamification as a tool for remediation of engagement, motivation, and collaboration. However, the literature showed that the structural and contextual deployment of game elements is defined only partially in practice. Subsequently, gamification suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 30 publications
(23 reference statements)
1
11
0
Order By: Relevance
“…Höllig, Tumasjan, and Welpe (2020) studied leaderboard design related to the role of competitiveness in learning. Further, Imran (2019) showed a positive relationship between digital badges and student engagement in gamified e-learning systems. Such technical aspects of gamification and serious games, although imperative, are beyond the scope of this study.…”
Section: Technical Aspectsmentioning
confidence: 94%
See 1 more Smart Citation
“…Höllig, Tumasjan, and Welpe (2020) studied leaderboard design related to the role of competitiveness in learning. Further, Imran (2019) showed a positive relationship between digital badges and student engagement in gamified e-learning systems. Such technical aspects of gamification and serious games, although imperative, are beyond the scope of this study.…”
Section: Technical Aspectsmentioning
confidence: 94%
“…Digital badges, leaderboards, and scoring points have become prominent in gamification (Mekler, et al, 2017). Adding gamification elements can improve motivation and engagement (Imran, 2019;Özhan and Kocadere, 2020). Gamification elements are used in consumer energy consumption applications to reduce consumption and foster sustainability (Mulcahy, Russell-Bennett and Iacobucci, 2020), smart cities to reduce traffic (Cellina, et al, 2020), marketing applications to increase customer commitment, willingness to pay, and to provide customer referrals (Wolf, Weiger and Hammerschmidt, 2020).…”
Section: Gamificationmentioning
confidence: 99%
“…Abramovich et al [5] studied the effect of merit and achievement badges, used in an intelligent tutor for teaching mathematics to middle-school students. In contrast, Imran [7] used badges for gamifying a learning environment, helping students prepare for entrance exams to higher education institutions. Kyewski and Krämer [14] studied the impact of badges awarded for performance of specific activities within a graduate-level elearning seminar on Computer-mediated Communication.…”
Section: Related Workmentioning
confidence: 99%
“…Most of the published empirical studies focused on investigating whether badges improve the students' engagement in the gamified activities and/or their academic achievements and as already pointed with contradicting results. Most of the authors, e.g., Hakulinen et al [13], Denny [20], Huang and Hew [19], Zainuddin [11], Imran [7], and Anderson et al [21] have found a positive effect of badges on student actions and on students' engagement with the gamified activities (practicing, question answering, online participation, out-of-class work). Concerning the student performance (course grades), some reported that the use of badges led to better student performance on the tests [11], to a reduced failing rate [13], or encouraged students to produce higher quality work [19].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation